Peptide tags for labeling membrane proteins in live cells with multiple fluorophores. (June 2005) - McCann, Corey M.; Bareyre, Florence M.; Lichtman, Jeff W.; Sanes, Joshua R.
We describe a method to label specific membrane proteins with fluorophores for live imaging. Fusion proteins are generated that incorporate into their extracellular domains short peptide sequences (13–38 amino acids) recognized with high affinity and specificity by protein ligands, α-bungarotoxin (BTX), or streptavidin (SA). Many fluorophore- and enzyme-conjugated derivatives of both ligands are commercially available. To demonstrate the general utility of the methods, we tagged a vesicle-associated protein (VAMP2), a receptor tyrosine kinase [muscle-specific kinase (MuSK)], and receptors for three neurotransmitters: acetylcholine (nAChRα3), glutamate (mGluR2), and γ-aminobutyric acid (GABAA α3). In all cases, we could selectively label surface-exposed proteins without interference from intracellular pools. By successive pulse-labeling with different fluorophore conjugates of a single ligand, we were able to monitor endocytosis of tagged molecules. By combining the two ligands, we could assess co-localization of synaptic components in cells. This strategy for epitope tagging provides a useful adjunct to green fluorescent protein (GFP)-tagging, which fails to distinguish intracellular from extracellular pools, sometimes interferes with protein localization or function, and requires a separate construct for each color.